Effect of feeding type 2 diabetes mellitus rats with synbiotic yogurt sweetened with monk fruit extract on serum lipid levels and hepatic AMPK (5′ adenosine monophosphate-activated protein kinase) signaling pathway. Issue 9 (11th September 2020) - Ban, Qingfeng; Cheng, Jianjun; Sun, Xiaomeng; Jiang, Yunqing; Guo, Mingruo
Abstract : Monk fruit extract (MFE) is a natural sweetener that has been used as an ingredient of food and pharmaceutical products. Abstract : Monk fruit extract (MFE) is a natural sweetener that has been used as an ingredient of food and pharmaceutical products. The effects of feeding synbiotic yogurt fortified with MFE to rats with type 2 diabetes induced by high-fat diet and streptozotocin on serum lipid levels and hepatic AMPK signaling pathway were evaluated. Results showed that oral administration of the synbiotic yogurt fortified with MFE could improve serum lipid levels, respiratory exchange rate, and heat level in type 2 diabetic rats. Transcriptome analysis showed that synbiotic yogurt fortified with MFE may affect the expression of genes involved in binding, catalytic activity, and transporter activity. The Kyoto Encyclopedia of Genes and Genomes enrichment analysis revealed that these differentially expressed genes were related to AMPK signaling pathway, linoleic acid metabolism, and α-linolenic acid metabolism. Western blotting confirmed that synbiotic yogurt fortified with MFE could activate AMPK signaling and improve the protein level of the hepatic gluconeogenic enzyme G6Pase in diabetic rats. The results indicated that MFE could be a novel sweetener for functional yogurt and related products.